(untitled) (Revista de Ciências Agroveterinárias, 2013)
Paracetamol intoxication in cats occurs due to accidental or iatrogenic exposure, when the owners administers the medication with the intention of treating their pet. Cats are deficient in terms of biotransformation, so even small doses of the drug can cause toxicity. Among the clinical signs, cyanosis, depression, icterus, edema of face and limbs, tachypnea, dyspnea, anorexia, weakness, vomiting, hypothermia and hematuria can be observed. Fortunately, with aggressive treatment and appropriate supportive care, most animals are able to recover completely. Owners should be advised not to administer acetaminophen in cats. Considering the large number of cats treated in emergency veterinary with clinical signs of acetaminophen toxicity, we have the objective of presenting information about this disease for clinicians of small animals to identify the framework and thus treat it successfully.